Impact of strain induced by polymer curing in benzocyclobutene embedded semiconductor nanostructures. Issue 12 (25th September 2014) - Bussone, Genziana; Dimakis, Emmanouil; Grifone, Raphael; Biermanns, Andreas; Tahraoui, Abbes; Carbone, Dina; Geelhaar, Lutz; Schülli, Tobias U.; Pietsch, Ullrich
<x xml:space="preserve">Abstract</x> Polymers such as benzocyclobutene are commonly used as embedding materials for semiconductor nanostructures. During the curing process of the polymer up to 250 °C, a significant impact of strain can be induced on the embedded semiconductor material due to different thermal expansion coefficients. This strain has been revealed by X‐ray diffraction in free‐standing GaAs nanowires grown on a silicon substrate, embedded in a polymer matrix. It will be shown that this strain is released during the X‐ray irradiation if additionally an external static electric field is applied. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> (© 2014 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)